Circular RNA Foxo3 Relieves Myocardial Ischemia/Reperfusion Injury by Suppressing Autophagy via Inhibiting HMGB1 by Repressing KAT7 in Myocardial Infarction - Sun G; Shen JF; Wei XF; Qi GX (Dove Medical Press, 2021)
Guang Sun,1 Jian-Fen Shen,2 Xiu-Fang Wei,1 Guo-Xian Qi1 1Department of Geriatric Cardiology, The First Affiliated Hospital of China Medical University, Shenyang, Liaoning, 110001, People's Republic of China; 2Department of Cardiology, The First Affiliated Hospital of China Medical University, Shenyang, Liaoning, 110001, People's Republic of ChinaCorrespondence: Guo-Xian Qi Email xianzhanza784@126.comIntroduction: Myocardial infarction is coronary artery-related heart disease, and the leading cause of mortality globally. Circular RNAs (circRNAs) are a new type of regulatory RNAs and participate in multiple pathological cardiac progression.Methods: However, the function of circFoxo3 in MI-induced myocardial injury remains obscure.Results: Significantly, we identified that circFoxo3 was downregulated in the MI rat model and the overexpression of circFoxo3 ameliorated MI-induced cardiac dysfunction and attenuated MI-induced autophagy in rat model. Meanwhile, the overexpression of circFoxo3 repressed oxygen-glucose deprivation (OGD)-induced autophagy, apoptosis, inflammation, and injury of cardiomyocyte in vitro. Mechanically, we identified that the expression of KAT7 was reduced by circFoxo3 overexpression in cardiomyocytes. Meanwhile, the expression of HMGB1 was repressed by the depletion of KAT7 in cardiomyocytes. The enrichment of histone H3 lysine 14 acetylation (H3K14ac) and RNA polymerase II (RNA pol II) on HMGB1 promoter was inhibited by the knockdown of KAT7. Moreover, the overexpression of circFoxo3 suppressed HMGB1 expression and KAT7 overexpression rescued the expression of HMGB1 in cardiomyocytes. The enrichment of KAT7, H3K14ac, and RNA poly II on HMGB1 promoter was decreased by circFoxo3 overexpression, while the overexpression of KAT7 could reverse the effect. The overexpression of KAT7 or HMGB1 could reverse circFoxo3-attenuated cardiomyocyte injury and autophagy in vitro. Thus, we conclude that circular RNA circFoxo3 relieved myocardial ischemia/reperfusion injury by suppressing autophagy via inhibiting HMGB1 by repressing KAT7 in MI.Discussion: Our finding provides new insight into the mechanism by which circFoxo3 regulates MI-related cardiac dysfunction by targeting KAT7/HMGB1 axis.Keywords: myocardial infarction, autophagy, circFoxo3, KAT7, HMGB1